Caloric Restriction in Group-Housed Mice: Littermate and Sex Influence on Behavioral and Hormonal Data - Perea, Cristina; Vázquez-Ágredos, Ana; Ruiz-Leyva, Leandro; Morón, Ignacio; Zúñiga, Jesús Martín; Cendán, Cruz Miguel (Frontiers in Veterinary Science, 2021)
Abstract Much of the research done on aging, oxidative stress, anxiety, and cognitive and social behavior in rodents has focused on caloric restriction (CR). This often involves several days of single housing, which can cause numerous logistical problems, as well as cogni-tive and social dysfunctions. Previous results in our laboratory showed the viability of long-term CR in grouped rats. Our research has studied the possibility of CR in grouped female and male littermates and unrelated CB6F1/J (C57BL/6J × BALBc/J hybrid strain) mice, measuring: (i) possible differences in body mass proportions between mice in ad libitum and CR conditions (at 70% of ad libitum), (ii) aggressive behavior, using the number of pushes and chasing behavior time as an indicator and social behavior us-ing the time under the feeder as indicator, and (iii) difference in serum adrenocortico-tropic hormone (ACTH) concentrations (stress biomarker), under ad libitum and CR conditions. Results showed the impossibility of implementing CR in unrelated male mice. In all other groups, CR was possible, with a less aggressive behavior (measured only with the number of pushes) observed in the unrelated female mice under CR condi-tions. In that sense, the ACTH levels measured on the last day of CR showed no differ-ence in stress levels. These results indicate that implementantion of long-term CR in mice can be optimized technically and also related to their well-being by grouping ani-mals, in particular, related mice.